2021
DOI: 10.1002/pep2.24245
|View full text |Cite
|
Sign up to set email alerts
|

Peptides and peptidomimetics as therapeutic agents for Covid‐19

Abstract: The severe acute respiratory syndrome coronavirus‐2 (SARS‐CoV‐2) Covid‐19 pandemic has caused high morbidity and mortality rates worldwide. Virus entry into cells can be blocked using several strategies, including inhibition of protein‐protein interactions (PPIs) between the viral spike glycoprotein and cellular receptors, as well as blocking of spike protein conformational changes that are required for cleavage/activation and fusogenicity. The spike‐mediated viral attachment and entry into cells via fusion of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 126 publications
(207 reference statements)
0
7
0
Order By: Relevance
“…[110]. Furthermore, it has previously been discussed that furin-interfering medications include 1-antitrypsin Portland (1-PDX) [117,118], crude drugs which contain honokiol [119], chloromethylketone (CMK), and naphthofluorescein demonstrated antiviral effects on SARS-CoV-2-infected cells by reducing virus replication as well as cytopathic effects [120], Decanoyl and obatoclax inhibitors [121,122], and peptides and peptidomimetics [123]. To the best of our knowledge, no furin inhibitor small molecules with high specificity and good effects have been discovered.…”
Section: In Silico-based Studies Targeting Furinmentioning
confidence: 99%
“…[110]. Furthermore, it has previously been discussed that furin-interfering medications include 1-antitrypsin Portland (1-PDX) [117,118], crude drugs which contain honokiol [119], chloromethylketone (CMK), and naphthofluorescein demonstrated antiviral effects on SARS-CoV-2-infected cells by reducing virus replication as well as cytopathic effects [120], Decanoyl and obatoclax inhibitors [121,122], and peptides and peptidomimetics [123]. To the best of our knowledge, no furin inhibitor small molecules with high specificity and good effects have been discovered.…”
Section: In Silico-based Studies Targeting Furinmentioning
confidence: 99%
“…Recently, there have been many reports of development of fusion inhibitors based on the SARS-CoV-2 HR2 region, including the HR2 region peptide itself and its stapled peptides, [10][11][12][13] and EK1, which was derived from the HR2 region of an a-coronavirus strain HCoV-OC43 and its C-terminally lipidated peptides. 14,15 It is also reported that the HR2 region in the S2 unit is highly conserved among the existing mutants of SARS-CoV-2 from the alpha strain to the omicron strain (B.1.1.529).…”
Section: Introductionmentioning
confidence: 99%
“…1 Chemists used the approach of introducing chemical changes in the peptide backbone or side chains in order to improve the physical and chemical properties of the parent peptides, predicting their promising potentials as candidates for medicinal, environmental and industrial applications. [2][3][4][5][6] Among the modications in the peptide backbone are those occurring on the amide bond leaving the side chains without any changes. 7 Peptide backbones can be modi-ed in various ways either by extending the peptide chain by one more atom (s) or by changing at least one peptide bond with an isosteric or isoelectronic surrogate, depsipeptide, ketomethylene isoester, 8 azapeptide, 8,9 retro-inverso, 10,11 aminoxy acid, 12,13 hydrazino acid, 14,15 or b-amino acid.…”
Section: Introductionmentioning
confidence: 99%